Cost Comparison of Various Brands of Antihypertensives in the Indian Market with Drug Price Control Order List: An On-Foot Survey - V, Aditya; Sirish, Pragathi; Hegde, Nandita Parameshwar; A M, Sinchana Patel; S, Chitra Shree; B S, Girish (Indian Journal of Pharmacy Practice)
Background and Rationale: There are more than ten distinct categories of medications for hypertension, each with a different price tag. DPCO is the price list that provides the price cap of branded medications whereas CIMS and IDT are publications that provide the actual marketing price of available brands. Hence this study aimed to compare the DPCO pricing with the neighborhood pharmacies in south Bengaluru. Materials and Methods: The ceiling price for NLEM-listed antihypertensives was collected from DPCO 2013 (updated in 2018) and retrieved from the NPPA website and the marketed price of the same was collected from CIMS India (October 2022-January 2023) and IDT (July 2022-October 2022). An On-foot survey was conducted at nearby pharmacies and the same was compared. Results: Telmisartan 40 mg had the most substantial number of brands (51 brands) out of the 212 brands in CIMS-India and was sold above the DPCO recommended ceiling price. Out of 216 brands listed in IDT, Amlodipine 5mg was found to have a greater number of brands with Telmisartan 80 mg being sold greater than recommended price cap. There were 141 commercial brands for 17 different AHAs in local Pharmacies with Telmisartan 20 mg having the most brands and Ramipril 2.5 mg and 5 mg being sold above the fixed ceiling price. Conclusion: The majority of antihypertensives are profitability oppressed in a nebulous way. Government should revitalize pharmaceutical operations and broaden the present National List of Essential Medicines.
Keywords: Cost Comparison; Antihypertensive; DPCO; CIMS-India; India Drug Today; Local Community Pharmacy